2022
DOI: 10.3390/su14137564
|View full text |Cite
|
Sign up to set email alerts
|

New Characteristics in the Fermentation Process of Cocoa (Theobroma cacao L.) “Super Árbol” in La Joya de los Sachas, Ecuador

Abstract: In Ecuador, since 2005 in the northern Amazon, trinitario hybrid cacao mother plants characterized by early and abundant fruiting, known as “Super árbol”, have been identified. This genetic material was disseminated in the region, but most of the available information corresponds to empirical knowledge. In this sense, the present study aimed to evaluate different fermentation techniques in the “Super árbol” cocoa by analyzing physical and chemical variables in the climatic conditions of the Joya de Los Sachas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Based on the results of the research that has been done, it can be concluded that the concentration of cocoa bean extract has an effect on the formation of clear zones on Streptococcus mutans bacteria. As in the research, Streptococcus mutans has antibacterial properties (Kiros et al, 2022), and cocoa bean extract as a natural material in inhibiting the growth of Streptococcus mutans (Sanchez-Capa et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of the research that has been done, it can be concluded that the concentration of cocoa bean extract has an effect on the formation of clear zones on Streptococcus mutans bacteria. As in the research, Streptococcus mutans has antibacterial properties (Kiros et al, 2022), and cocoa bean extract as a natural material in inhibiting the growth of Streptococcus mutans (Sanchez-Capa et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Cocoa (Theobroma cacao L.) is a plantation crop that provides income to more than 4.5 million families globally [1]. Approximately 89% of the production is supplied by Ghana, Ivory Coast, Nigeria, Cameroon, New Guinea, Brazil, Indonesia, and Ecuador [2]. Indonesia is the third-largest cocoa-producing country in the world, contributing about 15% of global cocoa production [3].…”
Section: Introductionmentioning
confidence: 99%
“…Theobroma cacao (Cocoa) is considered one of the most important raw materials in international trade; it is a source of foreign exchange in 58 producing countries, highlighting that 89% of this production is found in Ivory Coast, Ghana, Indonesia, Nigeria, Brazil, Ecuador, Malaysia and Cameroon [1]. Cocoa production is sometimes affected by environmental, physical, and chemical factors and inadequate pest and disease control [2].…”
Section: Introductionmentioning
confidence: 99%